A new genus and species of ilyophine eel (Anguilliformes: Synaphobranchidae: Ilyophinae) from the Arabian Sea, western Indian Ocean - Tighe, Kenneth A.; Kodeeswaran, Paramasivam (Zootaxa, 2025)
A new genus and species of ilyophine eel, Branchenchelys megacephala, is described based on five specimens collected in the Arabian Sea, western Indian Ocean. The new genus is distinguished from all other ilyophine genera by its relatively large head with large gill openings and a very large branchial chamber with an increased number of branchiostegal rays and hypertrophied gill filaments.